Linguistic Characteristics of Narrative Text Written by Male and Female Students - Nurul Hasanah; Zainuddin .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2020)
Language is a reflection of speakers. A person can guess the identity such as the origin, character, or behavior of the interlocutor of the language he uses. Gender affect the use of language, both oral and written language. As an essential skill in learning English, writing involves the application of grammar and sentence pattern, vocabulary, or diction and cross cultural understanding. It can be said that writing ability is someone capability to express their idea in the form of written representation. The objective of this study is to investigate the linguistic form of narrative text written by male and female students. The data of this study will be gathered by sentences in narrative text written by male and female students of Senior High School about their experience. The use of language features proposed empty adjectives, hedge, intensifier, hypercorrect grammar super polite form, tag question and emphatic stress, even though the characteristics of color words and question intonation have not been found in the characters’ utterances. Keywords: Linguistic Characteristics, Gender, Writing, Narrative Text